Linear Selective Hydroformylation of 2‐Arylpropenes Using Water‐Soluble Rh‐PNP Complex: Straightforward Access to 3‐Aryl‐Butyraldehydes. Issue 24 (3rd November 2021) - Ru, Tong; Liang, Guanfeng; Zhang, Luyun; Ning, Yingtang; Chen, Fen‐Er
Abstract: Straightforward access to 3‐aryl‐butyraldehydes was developed through the aqueous biphasic Rh‐catalyzed hydroformylation of 2‐arylpropenes using a water‐soluble PNP ligand. This protocol accommodates broad substrate scope with high yields (up to 95 %) and excellent linear selectivity (>99 : 1 b/l ratio). The synthesis of rac‐ar ‐turmerone and the gram‐scale hydroformylation further demonstrated the practical nature of this method. Abstract : Rh‐catalyzed hydroformylation of 2‐arylpropenes becomes available using an unprecedented PNP ligand. The protocol provides a powerful strategy to access a wide library of 3‐aryl‐butyraldehydes with excellent selectivity and scalability. A concise total synthesis of rac‐ar ‐turmerone is also pursued to demonstrate the practical nature of this protocol.